URGENSI PEMBENTUKAN UNDANG-UNDANG LEMBAGA KEPRESIDENAN DALAM MEWUJUDKAN PEMILIHAN UMUM BERINTEGRITAS DI INDONESIA - Aditya Andela Pratama,; Syaif Al Haq,; Adelia Mizani Qisti, (JIL : Journal of Indonesian Law, 2024)
This study aims to analyze the urgency of establishing the Presidential Institution Law as an effort to improve election integrity. This research uses normative juridical method with statutory, conceptual, comparative, and historical approaches. This research uses legal materials in the form of Constitutional Court Decision 1/PHPU.PRES-XXII/2024 (Anies-Muhaimin), Decision Number 2/PHPU.PRES-XXII/2024 (Ganjar Mahfud), the Draft Law on Presidential Institutions and other legal materials relevant to this research. The results show that the establishment of a special law on presidential institutions is needed to clarify the limits of the president's authority during the election period, especially in terms of the use of state resources, political influence, and intervention in the democratic process. These restrictions will reduce the potential for conflicts of interest and abuse of power, thereby creating a more transparent, fair and integrity mechanism in elections.